A seriedade do risível: uma análise de crônicas de Luís Fernando Veríssimo - Resina, Maria Madalena (2009)
The present dissertation aimed at studying the laughter manifestation and the risible in Luís Fernando Veríssimo s chronicles, especially in Bobos I (1982) and Ri, Gervásio (1987) which, according to the humor theory, emphasizes both, the laughter ambivalence and ambiguity, principally its serious perspective. Firstly, it is briefly explained the main characteristics of the chronicle genre, in which Veríssimo s humor it is manifested. The objective is to observe a certain relationship between genre and the object of study. Secondly, inside the risible context, it is pointed out not only the differences between the humorous and humor, based on the Pirandello s work (1996), but also the imprecisions which involve the humorous, according to Propp (1992) arguments and other authors, and the most part of them it is mentioned by him. It is exposed some of the humoristic characteristics used in the present study manifesting a ludic laughter and, above all, a reflexive laughter, which is proper of humor. Apart from that, an overview of Veríssimo s biography was developed, pointing out his mainly works, his way of writing and peculiar style. The referred chronicles which composed this research corpus were analyzed employing the language resources related to the humorous and humor. In order to conclude, anguish is presented not only as a strategy and a language phenomenon, but mainly as a powerful tool that the author makes use to critically portray situations which brings to light the anguish, the weakness and the human addictions, and also to provoke into the reader s mind a reflexive analysis on such situation